Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(B=\left(\frac{15}{16}+\frac{1}{17}\right)-\left(\frac{15}{16}-\frac{16.11}{17.11}\right)\)
\(B=\frac{15}{16}+\frac{1}{17}-\frac{15}{16}+\frac{16}{17}\)
\(B=\frac{1}{17}+\frac{16}{17}=\frac{17}{17}=1\)
=\(\left(\frac{15}{16}+\frac{1}{17^5}\right)+\left(\frac{16}{17}-\frac{15}{16}\right)\)
=\(\frac{1}{17^5}+\frac{16}{17}=\frac{1+16.17^4}{17^5}\)
đáp số là số thập phân vô hạn không tuần hoàn
\(\left(\frac{151515}{161616}+\frac{17^9}{17^{10}}\right)-\left(\frac{1500}{1600}-\frac{1616}{1717}\right)\)
\(=\left(\frac{15}{16}+\frac{1}{17}\right)-\left(\frac{15}{16}-\frac{16}{17}\right)\)
\(=\frac{15}{16}+\frac{1}{17}-\frac{15}{16}+\frac{16}{17}\)
\(=\left(\frac{15}{16}-\frac{15}{16}\right)+\left(\frac{1}{17}+\frac{16}{17}\right)\)
\(=\frac{15-15}{16}+\frac{1+16}{17}\)
\(=0+\frac{17}{17}\)
\(=0+1\)
\(=1\)
\(B=\left(17+\dfrac{1}{25}-16-\dfrac{11}{15}\right)\cdot\dfrac{75}{23}+\dfrac{75}{23}\cdot\dfrac{23}{75}\)
\(=\dfrac{23}{75}\cdot\dfrac{75}{23}+1=1+1=2\)
a: \(=\left(\dfrac{17}{10}+\dfrac{70}{10}-\dfrac{87}{10}\right):\left(\dfrac{23}{4}-\dfrac{11}{4}+\dfrac{9}{25}\right)\cdot\left(12,98\cdot0,25\right)+12,5\)
\(=0:\left(3+\dfrac{9}{25}\right)\cdot\left(12,98+0,25\right)+12,5\)
=12,5
b: \(=\dfrac{13}{12}\cdot\dfrac{27}{5}\cdot2\cdot\dfrac{34}{9}\cdot2\cdot\dfrac{2}{17}\)
\(=\dfrac{13}{12}\cdot2\cdot\dfrac{27}{5}\cdot\dfrac{34}{9}\cdot\dfrac{4}{17}\)
\(=\dfrac{13}{6}\cdot\dfrac{27}{5}\cdot\dfrac{8}{9}=\dfrac{8}{6}\cdot3\cdot\dfrac{13}{5}=4\cdot\dfrac{13}{5}=\dfrac{52}{5}\)
11) \(\dfrac{5}{7}\left(\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{4}{7}\right)+\left(\dfrac{1}{3}-\dfrac{1}{2}-\dfrac{4}{7}\right):\dfrac{7}{5}\)
= \(\dfrac{5}{7}\left(\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{4}{7}\right)+\left(\dfrac{1}{3}-\dfrac{1}{2}-\dfrac{4}{7}\right)\cdot\dfrac{5}{7}\)
= \(\dfrac{5}{7}\left(\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{4}{7}+\dfrac{1}{3}-\dfrac{1}{2}-\dfrac{4}{7}\right)\)
= \(\dfrac{5}{7}\cdot0\)
=0
12) \(\dfrac{43}{5}\left(\dfrac{17}{3}-\dfrac{16}{9}+2\right)-\dfrac{43}{5}\left(\dfrac{17}{3}-\dfrac{16}{9}\right)\)
= \(\dfrac{43}{5}\left(\dfrac{17}{3}-\dfrac{16}{9}+2-\dfrac{17}{3}+\dfrac{16}{9}\right)\)
= \(\dfrac{43}{5}\cdot2=\dfrac{43}{10}\)
11, 5/7( 1/2-1/3+1/4)+ (1/3-1/2-1/4):7/5
= 5/7.(1/2 - 1/3 + 1/4 )+( 1/3 - 1/2 - 1/4). 5/7
= 5/7.(1/2 - 2/3 + 1/4 + 1/3 - 1/2 - 1/4)
= 5/7 . -1/3
= -5/21
12, 43/5.(17/3 - 16/9 + 2)- 43/5. (17/3 - 16/9)
= 43/5.( 17/3 - 16/9 + 2 - 17/3 + 16/9)
= 43/5 . 2
= 86/5
\(B=\left(\frac{151515}{161616}+\frac{17^9}{17^{10}}\right)-\left(\frac{1500}{1600}-\frac{176}{187}\right)\)
\(B=\left(\frac{15}{16}+\frac{1}{17}\right)-\left(\frac{15}{16}-\frac{16}{17}\right)\)
\(B=\frac{15}{16}+\frac{1}{17}-\frac{15}{16}+\frac{16}{17}\)
\(B=\left(\frac{15}{16}-\frac{15}{16}\right)+\left(\frac{1}{17}+\frac{16}{17}\right)\)
\(B=0+1=1\)
Vậy: B=1